Calibration of HVI cotton elongation measurements - Christopher D. DELHOM; Eric F. HEQUET; Brendan KELLY; Noureddine ABIDI; Vikki B. MARTIN (Journal of Cotton Research, 2020)
Abstract Background The strength of cotton fiber has been extensively studied and significant improvements in fiber strength have been made, but fiber elongation has largely been ignored, despite it contributing to the energy needed to break fibers, which affects fiber handling and processing. High Volume Instruments (HVI) measure fiber elongation but have not been calibrated for this property, making the measurement unavailable for comparative work among instruments. In prior work, a set of elongation calibration materials had been developed based on Stelometer results. A round trial of ten Australian and U.S. instruments was conducted on six cotton samples representing a range of 4.9% to 8.1% elongation. Results By scaling the HVI elongation values of each instrument to the values of the two calibration samples, the coefficient of variation in instrument measurements was reduced from an average of 34% for the uncalibrated measurements to 5% for the calibrated measurements. The reduction in variance allows for the direct comparison of results among instruments. A single-point elongation calibration was also assessed but found to be less effective than the proposed two-point calibration. Conclusion The use of an effective calibration routine on HVI measurement of cotton significantly reduces the coefficient of variation of the elongation measurement within and between instruments. The implementation of the elongation calibration will allow testing and breeding programs to implement high-speed elongation testing which makes the use of elongation values possible in breeding programs.